KEDUDUKAN DAN FUNGSI BAHASA BALI PADA MASYARAKAT ISLAM DI BANJAR CANDIKUNING II KECAMATAN BATURITI KABUPATEN TABANAN - Sosiawan, Putu (Humanis; Volume 9. No. 2. November 2014, 2014)
The focus of the study is "The status and function of Balinese language in the Islamic Society Banjar Candikuning II Baturiti, Tabanan Regency". This study used sociolinguistic theory which refers to the topic of bilingualism. This study aims to identify and describe the position and function of Balinese language in the Islamic community in Balai Banjar Candikuning II Baturiti, Tabanan Regency. The method used in providing data is the method of observation with the questionnaire technique, watching, and interview techniques followed by recording and taking notes. Furthermore, in the data analysis, descriptive qualitative method and supported by quantitative method is used. The presentation of data analysis used formal methods and informal techniques of deductive – inductive, inductive – deductive. The results of this study indicate that; (1) position of Balinese Language in Islamic societies in Banjar Candikuning II Baturiti Tabanan is the mother tongue for most people, (2) Balinese language has a very important function in the life of society,.
Keywords: Status, Functions, and the Islamic Society